Organisational form, risk-taking, and performance: an empirical study of UK unit trust companies - Shinozawa, Yoshikatsu (2004)
Following privatisations in the 1980's, the UK financial industry embarked on a series of demutualisations, which developed into a global trend in the late 1990's. This structural shift has generated numerous debates in academic circles concerning various managerial issues of mutual versus stock owned companies. Informed by agency theory, this thesis contributes to this debate by exploring the link between ultimate organisational form and the behaviour of companies in the UK unit trust industry. The UK unit trust fund industry provides an excellent environment to explore this line of research because ultimate organisational form varies, and because the intra-industry variations are far smaller than those of other industries in term of regulations, income structure, and the use of information technology.